HR Re-engineering Elevates Banking Performance in Commercial Banks: Rekayasa Ulang SDM Meningkatkan Kinerja Perbankan di Bank Umum - Dr. Ali Kadhim Saddam; Mr. Oday Hussein Ali; Mr.Rafid Khudhur Radhi Alsaedi (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Re-engineering human resources (HR) is a critical method for enhancing organizational efficiency and performance, especially in sectors like banking where customer satisfaction, employee satisfaction, profit growth, and diversity of services are pivotal. Specific Background: This research investigates the impact of HR re-engineering on banking performance, focusing on organizational, human, and technological dimensions. Knowledge Gap: Despite extensive studies on HR re-engineering, its direct correlation with banking performance, particularly in commercial banks, remains underexplored. Aims: The study aims to clarify and apply HR re-engineering methods to improve banking performance, using a questionnaire, personal interviews, and field observations on a random sample of 200 respondents, analyzed via SMART PLS software. Results: Statistical analysis revealed a significant correlation between HR re-engineering and improved bank performance. Key findings indicate that HR re-engineering enhances employee morale and organizational efficiency, ultimately boosting customer satisfaction, employee satisfaction, profit growth, and service diversity. Novelty: This study uniquely combines multiple data collection methods and advanced statistical analysis to provide robust evidence of the positive impact of HR re-engineering on banking performance. Implications: The findings suggest that banks should invest in HR re-engineering programs, focusing on training, skill development, and technological integration to improve performance. These programs should be supported by adequate material and financial resources to ensure their success, thereby enhancing the competitive edge of banks in a dynamic environment. Highlights: Correlation and Impact: HR re-engineering boosts banking performance significantly. Methodology: Used questionnaires and SMART PLS for robust analysis. Implementation: Invest in HR training and technology for enhanced competitiveness. Keywords: HR re-engineering, banking performance, customer satisfaction, employee satisfaction, SMART PLS